1997
DOI: 10.1071/c96061
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Aquatic Humic Substances with Manganese and Chromium

Abstract: Ultraviolet-visible and e.s.r. spectroscopies have been used to investigate the reactions of humic substances, extracted from swamp waters, with manganese(VII) and with chromium(VI). Potassium permanganate reacts quickly with humic substances to form manganese(II) derivatives. Phenolic groups are probably involved as a similar reaction occurs with simple phenols such as phenol and catechol. Manganese(II) interacts directly with carboxylate anionic groups in humic substances. E.s.r. spectroscopy shows that mang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 2 publications
3
4
0
Order By: Relevance
“…In [8] the concentration of the phenol group was reported to be 2.26 ± 0.72 (pK a unknown). Our results compare well with values (pK a values given at α HA = 0.5) of humic acids extracted from soils or waters [2,[9][10][11][12][13][14] or purchased from other companies (Wako [15], Fluka [16] and between 2.0 and 3.0 meq/g for the weaker sites (with pK a values from 5.0 to 6.4). Measurements of phenolic groups have not been reported as frequently but the capacity values for the phenolic groups range from 0.8 to 4.3 meq/g, while their pK a values vary from 8.9 ± 0.1 to 9.0 ± 0.2.…”
Section: Resultssupporting
confidence: 72%
“…In [8] the concentration of the phenol group was reported to be 2.26 ± 0.72 (pK a unknown). Our results compare well with values (pK a values given at α HA = 0.5) of humic acids extracted from soils or waters [2,[9][10][11][12][13][14] or purchased from other companies (Wako [15], Fluka [16] and between 2.0 and 3.0 meq/g for the weaker sites (with pK a values from 5.0 to 6.4). Measurements of phenolic groups have not been reported as frequently but the capacity values for the phenolic groups range from 0.8 to 4.3 meq/g, while their pK a values vary from 8.9 ± 0.1 to 9.0 ± 0.2.…”
Section: Resultssupporting
confidence: 72%
“…It was reported that chromate esters show characteristic absorption bands around 350-400 nm region of the spectrum and the most drastic band at 365 nm wavelength was ascribed to Cr(VI) oxy esters in the literature [19,20]. This distinct absorption band is similar to that reported by Lu et al, in the reaction of dichromate with humic substances which is known to be associated with the formation of Cr(VI) complex with diol, carboxylic acid, and polyphenol groups in humic substances [21].…”
Section: Preliminary Experimentssupporting
confidence: 81%
“…As reported by Gamble et al, hydrated manganese(II) ions and humic substances might form outer-sphere complexes in which manganese(II) ions remain partly hydrated at binding sites of humic acid [22]. It was also reported that manganese(II) interacts directly with carboxylate anionic groups in humic substances forming a weak complex with a log K value of 2.0 (±0.1) [21]. However, the complexation of manganese with humic acid could not be observed with UV-vis spectroscopy under the specified experimental conditions.…”
Section: Preliminary Experimentsmentioning
confidence: 82%
See 1 more Smart Citation
“…It is well known that uptake of chromates by plants produce long lived oxo-Cr V species that could afford dangerous effects to ecological cycles. 13 In soils, the presence of humic and fulvic acids contribute to the reduction of chromates generat-ing oxo-Cr V species 14 that can be absorbed by plants in contaminated soils. Low frequency EPR studies of plants contaminated with chromates have demonstrated that oxo-Cr V species are found predominantly in roots.…”
Section: Introductionmentioning
confidence: 99%